Novel diversity of Anaerolineae and Tepidiformia recovered from metagenomes of thermal microbial mats in Costa Rica - Brenes-Guillén, Laura; Vidaurre-Barahona, Daniela; Agüero, Kimberly; Ulloa, Andrés; Zuñiga, Yomara; Alvarado, Guillermo E.; Uribe-Lorío, Lorena (Frontiers in Microbiology, 2025)
Tropical thermal and mineral springs are ideal for studying microbial life in extreme environments, their microbial diversity, and functional profiles. In this study, we investigated the abundance and genomic diversity of the phylum Chloroflexota in microbial mats from 33 thermal and acidic springs across Costa Rica using 16S rRNA gene amplicon sequencing and shotgun metagenomics. Our results demonstrated that pH and temperature are the main environmental drivers shaping the abundance and diversity of Chloroflexota. Acidic conditions favored the presence of Ktedonobacteria and the candidate division AD3, while thermal environments were dominated by unclassified Anaerolineae. From a subset of thermal springs, we reconstructed 72 metagenome-assembled genomes (MAGs), many of which represent previously uncharacterized lineages. Comparative genomic analyses revealed two novel families and seven new genera within Anaerolineae and a distinct lineage within Tepidiformia. We proposed the following names: Ca. Sittenfelaceae, Ca. Mariellaceae, and Ca. Tepidiforma platanarica. Functional annotation of Anaerolineae and Tepidiformia MAGs suggested a degree of functional redundancy. Genes associated with methanogenesis, dissimilatory nitrate reduction, sulfur metabolism, and methylotrophy were detected, while genes involved in photosynthesis, nitrogen fixation, and nitrification were absent. Unique gene clusters were identified in each family, and interestingly, 23% of these unique genes were of unknown function, highlighting the unexplored genetic potential of these organisms. Canonical correspondence analysis (CCA) revealed that temperature significantly influences the microdiversity of Anaerolineae. Despite their taxonomic novelty, these lineages exhibit strong functional redundancy across major metabolic pathways, where overlapping metabolic capabilities may confer stability under fluctuating conditions and support the persistence of diverse Chloroflexota populations. This study provides the first genomic dataset of Chloroflexota from Central American geothermal environments and highlights tropical geothermal springs as reservoirs of novel microbial diversity and functional potential.